THE INFLUENCE OF GREEN FINANCE AND GREEN MARKETING ON SME PERFORMANCE: THE MODERATING ROLE OF INNOVATION CAPABILITY - Maria Dini Gilang Prathivi; Sihombing, Ririsma; Antonius Juniarto (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
The increasing global awareness of environmental sustainability has prompted businesses, including small and medium enterprises (SMEs), to adopt green finance and green marketing practices. However, the extent to which these strategies impact SME performance remains an important research area. This study aims to examine the influence of green finance and green marketing on SME performance, while also investigating the moderating role of innovation capability. A quantitative research approach is employed, using Structural Equation Modeling (SEM) to analyze data collected from SMEs that have implemented green finance and green marketing strategies. The results are expected to provide insights into how SMEs can leverage green financial resources and sustainable marketing approaches to enhance their performance, with innovation capability acting as a key enabler. The findings will contribute to both academic literature and practical applications, offering recommendations for SMEs to optimize their sustainability-driven strategies for competitive.